UPAYA MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN PKN PADA POKOK BAHASAN KERJASAMA NEGARA - NEGARA ASEAN MELALUI PENERAPAN METODE JIGSAW PADA SISWA KELAS VI DI SD NEGERI 007 KEPENUHAN HULU - Darti Darti (Indonesian Journal of Basic Education, 2020)
This study aims to find out the increase in student learning outcomes in Civics, the subject of the Cooperation of ASEAN Countries through the application of the Jigsaw method. the research method applied is classroom action research by applying the Cooperative Learning jigsaw model in grade VI SD N 007 Fullness of Hulu Rokan Hulu Regency with a total of 26 students. Teacher observation results show a good increase and change from cycle I meeting I to cycle II meeting II, from 75, 83.3, 91.7 to 95.8. Student learning outcomes show a good improvement and change from the first cycle of the first meeting to the second cycle of the second meeting, namely from 71.84, 75, 79.38 to 83.15. Teachers should use the Jigsaw method to provoke students' creativity in mastering the best possible material. through cooperative learning or collaborative learning helps students to learn, increase absorption, completeness, and improve student learning outcomes in Civics Subjects